Tensile Performance of Inter-Module Connections for Modular Steel Buildings Using Finite Element Method - Umi Arifatus Shoifah; Nur Ahmad Husin; Yuyun Tajunnisa (Institut Teknologi Sepuluh Nopember, 2025)
Steel modular construction is an innovative technology that uses prefabricated volumetric module unitsmanufactured in a factory and assembled on site via inter-module connections. However, this system's applicationin high-rise buildings is limited because the structural performance is strongly influenced by the inter-moduleconnection mechanism. This technology uses a translational spring model to transfer loads between modules throughinter-module connections. This approach uses threaded steel rod components, connection plates, shear keys, shearplates, and tie plates. This research aims to determine the maximum tensile capacity of the connection. It also aimsto study stress distribution due to tensile forces and failure modes in vertical modular connections. This researchuses the finite element method (FEM) to perform numerical analysis by applying monotonic loads. Simulation resultsindicate that the connection's maximum tensile capacity is 307.48 kN, distributed among two rods with capacities of153.74 kN each at a displacement of 23.2 mm. The rod undergoes elastic deformation up to Fy = 900 MPa, followedby a plastic phase up to nearly Fu = 1,100 MPa, causing permanent strain and necking. Tensile failure occurred dueto plasticity and necking conditions.